2021
DOI: 10.1155/2021/2567080
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of Multidrug-Resistant Tuberculosis Using Machine Learning Algorithms in SWAT, Pakistan

Abstract: In this paper, we have focused on machine learning (ML) feature selection (FS) algorithms for identifying and diagnosing multidrug-resistant (MDR) tuberculosis (TB). MDR-TB is a universal public health problem, and its early detection has been one of the burning issues. The present study has been conducted in the Malakand Division of Khyber Pakhtunkhwa, Pakistan, to further add to the knowledge on the disease and to deal with the issues of identification and early detection of MDR-TB by ML algorithms. These mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…GAs are stochastic search techniques, based on natural genetics, which provide robust search capabilities in complex spaces. A GA is an iterative process that solves an optimization problem [ 44 ]. Each solution is obtained by means of an encoding/decoding mechanism, which requires us to represent the solution as a chromosome.…”
Section: Methodsmentioning
confidence: 99%
“…GAs are stochastic search techniques, based on natural genetics, which provide robust search capabilities in complex spaces. A GA is an iterative process that solves an optimization problem [ 44 ]. Each solution is obtained by means of an encoding/decoding mechanism, which requires us to represent the solution as a chromosome.…”
Section: Methodsmentioning
confidence: 99%
“…The traditional modeling methods are not suitable for data with missing values, irregular spacing, and high-dimensional features. The majority of the current ML models are developed and evaluated either on artificially generated data or are experimental [11], [22], [43], [45], [55], [56]. In many cases, these models perform better than existing methods based on evaluation metrics such as accuracy and precision.…”
Section: Lack Of Models To Deal Directly With Real-world Datamentioning
confidence: 99%
“…Of the chronic diseases, TB, due to its infectious nature, increasing antimicrobial resistance and prevalence in low-and-middle-income (LMIC) countries, for example, India (32,48), Pakistan (49), Morocco (50), Kenya (51), and Uganda (13) has been widely studied. Characteristically, these previous studies gathered demographic and medical histories of a cohort and observed their adherence and outcomes.…”
Section: Use Of Machine Learning In Healthcarementioning
confidence: 99%
“…The researchers then retrospectively applied ML algorithms e.g. random forest, support vector machine (48,49), survival analysis (32,51), and logistic regression (13,50) to determine variables predictive of treatment failure or non-adherence.…”
Section: Use Of Machine Learning In Healthcarementioning
confidence: 99%
See 1 more Smart Citation